2020
DOI: 10.1177/0022034520906089
|View full text |Cite
|
Sign up to set email alerts
|

Decline in Dental Fluorosis Severity during Adolescence: A Cohort Study

Abstract: Dental fluorosis occurs from overingestion of fluoride during tooth formation. However, there is little evidence in the literature on whether or how fluorosis prevalence and severity change over time after tooth eruption. Permanent dentition dental examinations were conducted at ages 9, 13, 17, and 23 as part of the Iowa Fluoride Study, which has followed a cohort from birth. Fluorosis was assessed using the Fluorosis Risk Index (FRI) and Russell’s criteria for differential diagnosis. Measures of fluorosis sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 14 publications
3
13
0
3
Order By: Relevance
“…As occurred in the 2006–2008 birth cohorts, which showed DF frequencies of 73.0% (2015) and 98.7% (2018), the variation between the birth cohorts suggests the presence of different associated factors according to the period. Older children (2000–2002) showed the lowest DF frequency in 2018 (88.8%), which might indicate that some mild lesions may become clinically invisible over time, due to wear, leading to lower frequencies [ 24 ]. The age at which the clinical examination is performed is crucial to detect the disease clinically [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…As occurred in the 2006–2008 birth cohorts, which showed DF frequencies of 73.0% (2015) and 98.7% (2018), the variation between the birth cohorts suggests the presence of different associated factors according to the period. Older children (2000–2002) showed the lowest DF frequency in 2018 (88.8%), which might indicate that some mild lesions may become clinically invisible over time, due to wear, leading to lower frequencies [ 24 ]. The age at which the clinical examination is performed is crucial to detect the disease clinically [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the scientific literature, there is an unconfirmed theory that the prevalence of fluorosis and its severity increases over time after tooth eruption. However, recent studies have shown that very mild, mild and moderate fluorosis tends to decrease in severity in adolescence [29]. This trend continues into young adulthood and then slows down at the age of twenty.…”
Section: Discussionmentioning
confidence: 98%
“…Caries development in the primary dentition sets children on a steep trajectory toward further disease experience in the permanent dentition (Hall-Scullin et al 2017). Dental fluorosis, on the other hand, does not progress and may decline in severity over time (Do et al 2016; Curtis et al 2020). The trend of increasing fluorosis that prompted introduction of the policy measures has stabilized.…”
Section: Discussionmentioning
confidence: 99%